Medical Management of Obesity - Sang Yeoup Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
We, as health advocates, aim to raise awareness on the importance of a long-term approach for managing obesity as a chronic disease rather than merely a cosmetic issue. The cornerstone of obesity management remains the application of comprehensive lifestyle programs designed to modify dietary habits, physical activity, and behavior. Drug therapy for obesity should be used in addition to comprehensive lifestyle management. Appropriate use of anti-obesity drugs, approved by Food and Drug Administration, may help patients with obesity. Therefore, clinicians need to follow both a comprehensive and a personalized approach to treat obesity. Initially, it is necessary to assess patient's readiness to lose weight and to elicit the reasons and motivations for weight loss. Then, realistic goals should be set based on the patient’s health status. The goals include reducing and preventing comorbidities related to obesity. Even a modest weight loss, such as 5∼10% of total body weight, can significantly improve metabolic health. Finally, both the patient and the physician should be aware that weight maintenance is as important as weight loss.